Thursday
March 30, 2017

Post a New Question

Posted by on .

Find and simplify a) f(a), b) f(a + h) and c)
F(a+h) - f(a) / h ;

1. f(x) = x^2 + 5x -10

  • Algebra2 - ,

    f(a+h) = (a+h)^2 + 5(a+h) - 10
    f(a) = a^2 + 5a - 10

    (f(a+h)-f(a))/h
    = (a^2 + 2ah + h^2 + 5a + 5h - 10 - a^2 - 5a + 10)/h
    = (2ah + h^2)/h
    = 2a + h

  • Algebra2 - ,

    oops
    (2ah + 5h + h^2)/h
    = 2a + 5

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question